Characteristics and spectrum changes of PICU cases during the COVID-19 pandemic: a retrospective analysis - Yang, Yufan; He, Yueqi; Huang, Jiaotian; Yan, Haipeng; Zhang, Xinping; Xiao, Zhenghui; Lu, Xiulan (Frontiers in Pediatrics, 2024)
Objective: This study aims to compare the changes in the disease spectrum of children admitted to the Pediatric Intensive Care Units (PICU) during the COVID-19 pandemic with the three years prior to the pandemic, exploring the impact of the COVID-19 pandemic on the disease spectrum of PICU patients. Methods: A retrospective analysis was conducted on critically ill children admitted to the PICU of Hunan Children's Hospital from January 2020 to December 2022, and the results were compared with cases from the same period between January 2017 and December 2019. The cases were divided into pre-pandemic period (January 2017 to December 2019) with 8218 cases, and pandemic period (January 2020 to December 2022) with 5619 cases. General characteristics, age, and gender were compared between the two groups.Results: Compared to the pre-pandemic period, there was a 31.62% decrease in the number of admitted children during the pandemic period, and a 52.78% reduction in the proportion of respiratory system diseases.The overall mortality rate decreased by 87.81%. There were differences in age and gender distribution between the two periods. The length of hospital stay during the pandemic showed no statistical significance, whereas hospitalization costs exhibited statistical significance.: The COVID-19 pandemic has exerted a certain influence on the disease spectrum of PICU admissions. Implementing relevant measures during the pandemic can help reduce the occurrence of respiratory system diseases in children. Considering the changes in the disease spectrum of critically ill PICU children, future clinical prevention and treatment in PICUs should continue to prioritize the respiratory, neurological, and hematological oncology systems.